Formation Sequence of Different Spinel Species in Megacrystalline Peridotites of the Udachnaya-East Kimberlite Pipe (Yakutia): Evidence for the Metasomatism of Depleted Mantle - Lyudmila Pokhilenko (Minerals, 2019)
The large compositional variations in spinels from extremely depleted, megacrystalline harzburgite–dunites in the Udachnaya-East kimberlite pipe, Yakutia, apparently reflect multistage metasomatism. Changes in the redox regime are reflected in the compositions of different parts of mineral grains. From most reduced to most oxidized, spinel compositions divide into: (1) primary (rock-forming) Cr-spinel and spinel from the central parts of sulfide grains, (2) spinel from microcracks in olivine, (3) spinel in kelyphitic rim around garnet between garnet and olivine (Rim1 and Rim2 spinel), and (4) spinel in transformed kelyphitic rim around garnet between garnet and kimberlite (Rim3 spinel). P-T conditions for the vast majority of samples, calculated using the composition of primary Cr-spinel, fall in the diamond stability field. A change in the composition of spinels of different generations occurs along the sides of the classical triangle of spinel compositions Al–Cr–Fe3+: (1) Rim2 to Rim1 spinel—Al–Cr trend, (2) primary Cr-spinel to magnetite rim in the edge—Cr–Fe3+ (kimberlite) trend, (3) replacing Rim1 to Rim3—Al–Fe3+ trend.